Best Practices for Vocal Pedagogy with Gender Diverse People. Issue 2 (4th May 2022) - Azul, David; Quoresimo, Lisa
ABSTRACT: Due to a growing number of gender diverse people studying at university and presenting in voice clinics, teaching and clinical practices in the area of voice need to be adapted to allow students and clients to feel safe, supported, and appreciated in all aspects of who they are. In this article, the authors bring together perspectives from speech-language pathology, vocal pedagogy, gender, transgender, and feminist studies to illustrate the theoretical foundations and practical aspects of suggestions for a variety of best practices voice teachers can implement in their work with gender diverse people. The authors begin by situating themselves personally and professionally within the sociocultural contexts from which they write to illustrate the influences that have shaped their perspectives and to emphasize the located nature of their contributions to the topic area. Their suggestions are informed by culturally responsive and person-centered approaches to teaching and clinical practice and draw on a theoretical perspective that acknowledges the complexity and diversity of the experience and construction of gender in social interaction. Best practices and activities are suggested for teachers of both speech and song, and for classroom, theatrical and departmental level policies.